Variation and Evolution of the Whole Chloroplast Genomes of Fragaria spp. (Rosaceae) - Li, Chenxin; Cai, Chaonan; Tao, Yutian; Sun, Zhongshuai; Jiang, Ming; Chen, Luxi; Li, Junmin (Frontiers in Plant Science, 2021)
Species identification is vital for protecting species diversity and selecting high-quality germplasm resources. Wild Fragaria spp. comprise rich and excellent germplasm resources; however, the variation and evolution of the whole chloroplast (cp) genomes in the genus Fragaria have been ignored. In the present study, 27 complete chloroplast genomes of 11 wild Fragaria species were sequenced using the Illumina platform. Then, the variation among complete cp genomes of Fragaria was analyzed, and phylogenetic relationships were reconstructed from those genome sequences. There was an overall high similarity of sequences, with some divergence. According to analysis with mVISTA, non-coding regions were more variable than coding regions. Inverted repeats (IRs) were observed to contract or expand to different degrees, which resulted in different sizes of cp genomes. Additionally, five variable loci, trnS-trnG, trnR-atpA, trnC-petN, rbcL-accD, and psbE-petL, were identified that could be used to develop DNA barcoding for identification of Fragaria species. Phylogenetic analyses based on the whole cp genomes supported clustering all species into two groups (A and B). Group A species were mainly distributed in western China, while group B contained several species from Europe and Americas. These results support allopolyploid origins of the octoploid species F. chiloensis and F. virginiana and the tetraploid species F. moupinensis and F. tibetica. The complete cp genomes of these Fragaria spp. provide valuable information for selecting high-quality Fragaria germplasm resources in the future.